A public health and budget impact analysis of vaccinating the elderly and at-risk adults with the 23-valent pneumococcal polysaccharide vaccine or 13-valent pneumococcal conjugate vaccine in the UK. (December 2014) - Jiang, Yiling; Gauthier, Aline; Keeping, Sam; Carroll, Stuart
<x xml:space="preserve">Abstract</x> Objective: Since the introduction of the routine childhood immunization, a change in epidemiology of pneumococcal disease has been seen in both children and adults. This study aimed to quantify the public health and budget impact of pneumococcal vaccination of the elderly and those in at risk groups in the UK. Methods: The model was adapted from a previous population-based Markov model. At-risk adults and the elderly were assumed to receive PPV23 or PCV13 vaccination or no vaccination. Results: Over the study period (2012–2016), PPV23 vaccination led to a reduction in the number of invasive pneumococcal disease cases in most scenarios. The net budget impact ranged between £15 and £39 million (vs no vaccination) or between −£116 and −£93 million (vs PCV13). Conclusion: PPV23 vaccination program remains the optimal strategy from public health and budgetary perspectives despite epidemiological changes. PCV13 is likely to impose a significant budget with limited health benefits.